Evaluation of Adverse Outcome Predictors in Neonatal Seizure: A Longitudinal Study from a Tertiary Centre of Eastern India - Bidyut Kumar Khuntdar; Sumon Mondal; Surjit Naik; Mahesh Prasad Mohanta (JCDR Research and Publications Pvt. Ltd., 2023)
Introduction: Neonatal seizures are common but can be manifestations of serious underlying disorders and sometimes have a grave prognosis. Predictors for adverse outcomes are important for early referral and advanced interventions. Aim: To study the incidence and factors associated with neonatal seizure and to determine the predictors of adverse outcomes. Materials and Methods: This was a longitudinal study, conducted from April 2020 to March 2021 at a Rural Medical College (Midnapore Medical College and Hospital, West Bengal) in Eastern India. All the admitted newborns (N=143) in the Special Newborn Care Unit (SNCU), who had clinically evident seizures, were included in the study. Data were collected regarding the perinatal history, gestational age, type of delivery, birth weight, APGAR score at 1 and 5 minutes, and need for resuscitation at birth. The onset of the seizure, seizure type, investigation findings, possible aetiological diagnosis, and final outcome was noted. The management of neonatal seizures was as per the institutional protocol. Babies were followed up for a minimum of 28 days or throughout their hospital stay till discharge/death. The outcome was categorised into two categories: 'favourable' when there was a normal neurological examination and 'unfavourable' when there was any neurological impairment or death. Statistical analyses were performed using the Statistical Package for Social Sciences software version 25 (SPSS Inc., Chicago, IL, USA). Risk factors were determined by analysing outcomes using simple and multivariate logistic regression analysis. The p-values less than 0.05 were considered as statistically significant. Results: A total of 143 newborns had seizures out of 3126, making the incidence of neonatal seizures 4.57%. Males outnumbered females. Total 64.33% were preterm. Five minutes APGAR score <7 was noticed in 44.75%. The most common type was subtle seizure. Advanced resuscitation manoeuvre was required for 46.8% cases whereas mechanical ventilation was required in 11.88%. The most common aetiology was birth asphyxia (46.15%), and the cranial ultrasound showed Hypoxic Ishchaemic Encephalopathy (HIE) changes in 30.77% of cases. Multiple logistic regressions revealed only four factors, namely, preterm delivery (OR 5.82), need for extensive resuscitation manoeuvre (OR 6.21), presence of status epilepticus (OR 3.49) and abnormal cranial ultrasound (OR 1.02) to be the independent risk factors for unfavourable outcome. Conclusion: Clinical diagnosis of neonatal seizure could be useful in resource poor centers, where video-Electroencephalogram (EEG) is not available. Premature delivery, need for extensive resuscitation, presence of status epilepticus and abnormal cranial ultrasound were associated with poor short-term outcome.